Immunehistochemical and Histomorphological Study of Postnatal Development of the cecal tonsils in Turkey (Meleagris Gallopavo ) - Hussein, Ahmed.A.; Reshag, Ali. F. (The Iraqi Journal of Veterinary Medicine, 2019)
Forty normal turkeys divided into four age groups:1 week, 1 month, 2 months and 7 months. The cecal tonsils were separated and prepared for histological and Immunohistochemical studies. At 1 week old the tonsil appear as lymphoid aggregation of the lamina propria submucosa around central fossula. No septae among follicles, no germinal centers observed. At 1 month old the cecal portion which included the tonsil easily separated from other parts due to an increase cecal wall diameter was increased. The tonsil composed of a lot of tonsil crypts. The tissue septae among the crypts observed. At 2 and 7 months old the tonsils bulging from the internal surface of cecum toward the lumen as a rough large mass white to pink in color, germinal centers were present in the lymphoid follicles, the cecal tonsil diameter is increase with ages. The lymphocytes diameter is increasing with age also the internal surface of tonsil was lined with simple columnar epithelium (intestinal mucosa). The dimensions of cecal tonsils and lymphocytes measurements and tonsil mucosa are significantly increase with age. (CD268) antibody revealed presence of mature B lymphocytes within the parenchyma of bursa at two and seven month’s old turkey. CD8 no expressed at the first month age while different degrees of expression appeared at the other ages.